INTERPERSONAL RELATIONS EVIDENCED IN THE CLASSES OF ADAPTED MOTOR ACTIVITY (Fiep Bulletin - online, 2014)
The purpose of this descriptive study was to investigate the social interactions of children with disabilities participating in a program of adapted motor activity. For data collection we used the filming of two classes, whose theme was posture and locomotion and pre-sports, respectively, both consist of six activities. Were analyzed descriptively by array analysis of social interactions proposed by Zuchetto (2008). There were interpersonal relationships as physical contact, assistance, facial and verbal expressions in both classes. The choice of activities represented the starting point for the approach among participants. Interactions stood out from smiles and words of children with cerebral palsy and willingness to provide aid, like pushing the wheelchair of colleagues and demonstrate the tasks of a child with intellectual disabilities. These behaviors motivated children to accomplish tasks. It is noteworthy that most of the interactions occurred in tasks that required physical contact and personal assistance. Furthermore, it was noted that the relaxed atmosphere among children and adults auxiliary favored interactions that motivated and enabled children to engage. We conclude that motor activity classes for children with disabilities as well as benefit in the aspects neuromuscular, organic and interpretative, interferes positively in social and emotional skills resulting in improvements in self-esteem.
Keywords: Motor Activity adapted; Children with disabilities; social interactions